PENERAPAN MODEL PROBLEM BASED LEARNING UNTUKMENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR TINGKAT TINGGI (HOTS) PADA MATA PELAJARAN PPKn KELAS X DI SMA NEGERI 3 MUARA ENIM - Melianah (UNIB Press, 2024)
This Study aims to describe the application of Problem Based Learning Model to Improve High of Thinking Skill (HOTS) in PPKn subject of X grade At SMA Negeri 3 Muara Enim.The design of Study is used the action research and quasi experiment.The subjects are students of X grade of IPA.B in SMA Negeri 3 Muara Enim at the first semester In school year 2022/2023. Through the Simple Random technique that the sampling is resulted quasi experiment sample is X grade of IPS in SMA N 3 Muara Enim and X grade of IPA.A in SMA N 3 Muara Enim.The Instrument of Study used Observation Sheet and Test.The Data of research is analyzed by descriptive statistic, mean, percentage, and T- exam. The result of Study showed that the application of Problem Based Learning be able to improve the activity and skill in High Order of Thinking Skill (HOTS) X grade of SMA N 3 Muara Enim students